TEACHING MEDIEVAL LITERATURE AND CULTURE IN CONTEMPORARY UNIVERSITIES CHALLENGES AND OPPORTUNITIES FROM PAST TO PRESENT. EXEMPLARY CASE STUDIES OF THE ROMAN DE SILENCE AND MAURITIUS VON CRAÛN - Classen, Albrecht (Top Educational Review Journal (TERJ), 2022)
In the face of an ever-changing academic framework all scholars working with pre-modern literature, art history,philosophy, are currently deeply challenged to explain and justify their fields of investigation. More and more foreign and language departments in the United States decide to cut out the Middle Ages and the early modern period as irrelevant to their teaching and research portfolio. Nevertheless, medieval research continues strongly, as the wealth of relevant publications indicates, coupled with energetic conferences, symposia, and other activities. But there are hardly any academic job opportunities, which make it harder and harder to convince graduate students to pursue a degree in medieval literature, for instance. The present study does not promise to offer a panacea against this general malaise, but will indicate, through the close reading of two literary examples, the enormous potentialities of this primary material to attract students and to provide meaningful, relevant, and perhaps even transformative seminars on the undergraduate and graduate level